SORPTION-DESORPTION MECHANISM OF Zn(II) AND Cd(II) ON CHITIN - Sri Juari Santosa; Narsito Narsito; Aldes Lesbani (Indonesian Journal of Chemistry, 2006)
This study reports the results of the elucidation of the sorption-desorption mechanism of Zn(II) and Cd(II) on chitin through the determination of capacity, energy, and rate constant of sorption as well as the investigation of their desorption properties in NaCl and Na2EDTA solutions. The chitin was isolated through deproteination followed by demineralization of crab (Portunus pelagicus Linn) shell using NaOH solutions. The sorption of both metal ions followed the Langmuir isotherm model, resulting the sorption capacities of 3.2 x 10-4 and 2.8 x 10-4 mol g-1 for Zn(II) and Cd(II), respectively, and sorption energies of 15.1 kJ mol-1 for Zn(II) and 17.9 kJ mol-1 for Cd(II). It was also observed that Zn(II) was sorbed slightly faster than Cd(II) with first order sorption rate constants of 2.82 x 10-3 min-1 for Zn(II) and 2.61 x 10-3 min-1 for Cd(II). The result of the desorption experiment showed that Cd(II) and especially Zn(II) could only be exchanged by Na(I) after desorbing those metal ions by strong chelating agent of EDTA2-. The easier desorption of Zn(II) than Cd(II) by EDTA2- must be attributed by the smaller sorption energy of Zn(II) and by harder acid property of Zn(II) than Cd(II) as EDTA2- contained hard electron donor elements.